2021
DOI: 10.1002/ece3.7563
|View full text |Cite
|
Sign up to set email alerts
|

The interaction of resource use and gene flow on the phenotypic divergence of benthic and pelagic morphs of Icelandic Arctic charr (Salvelinus alpinus)

Abstract: Conceptual models of adaptive divergence and ecological speciation in sympatry predict differential resource use, phenotype–environment correlations, and reduced gene flow among diverging phenotypes. While these predictions have been assessed in past studies, connections among them have rarely been assessed collectively. We examined relationships among phenotypic, ecological, and genetic variation in Arctic charr ( Salvelinus alpinus ) from six Icelandic localities that have undergone va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 15 publications
(39 citation statements)
references
References 205 publications
0
37
1
Order By: Relevance
“…Þingvallavatn and Svínavatn showed the expected pattern with significant numbers of RDA outlier loci and regions located in high F ST regions. Moreover, the population with a relatively low amount of phenotypic and ecological divergence (Vatnshlíðarvatn) (Brachmann et al, 2021) showed no detectable RDA outliers. However, the low degree of phenotypic and ecological divergence between morphs in Vatnshlíðarvatn probably limits the statistical power of outlier detection methods, resulting in no detectable outliers.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Þingvallavatn and Svínavatn showed the expected pattern with significant numbers of RDA outlier loci and regions located in high F ST regions. Moreover, the population with a relatively low amount of phenotypic and ecological divergence (Vatnshlíðarvatn) (Brachmann et al, 2021) showed no detectable RDA outliers. However, the low degree of phenotypic and ecological divergence between morphs in Vatnshlíðarvatn probably limits the statistical power of outlier detection methods, resulting in no detectable outliers.…”
Section: Discussionmentioning
confidence: 99%
“…To detect genome wide signatures of selection associated with body shape and size variation, we characterized morphological variation using landmark‐based geometric morphometrics. The set of homologous landmarks used within these analyses have been previously defined and used in Brachmann et al (2021). Briefly, the analysis was based on 25 landmarks placed on individual images using TpsDig (Rohlf, 1990).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations